Influence of Repeated-Sprint Ability on the in-Game Activity Profiles of Semiprofessional Rugby Union Players According to Position - Glaise, Paul; Morel, Baptiste; Rogowski, Isabelle; Cornu, Brice; Martin, Cyril (Frontiers in Sports and Active Living, 2022)
This study investigated the influence of repeated-sprint ability (RSA) on the activity of rugby union players in a competitive situation according to their position. Thirty-three semiprofessional rugby union players (age, 25.6 ± 4.3; height, 184.0 ± 8.0 cm; weight, 98.9 ± 13.9 kg , ~20 h training a week), divided into two position subgroups (forwards n=20, backs n=13) or four positional subgroups (front row and locks n=13, back row n=7, inside backs n=6, outside backs n=7), were tested. Their RSA was assessed with a 12×20 m sprint test over a 20 s cycle. GPS data (distance, acceleration, number of sprints, maximum velocity and high-velocity running) and technical data were collected on 18 semiprofessional division rugby union games. In forwards, players with lower cumulated sprint time in the RSA test produced significantly more accelerations ( = -0.85, p < 0.001) and more combat actions per match minute ( = -0.69, p<0.001). In backs, RSA was significantly correlated with high-intensity running (distance ( = -0.76), Vmax ( = -0.84), sprints frequency ( = -0.71), high-velocity running ( = -0.76), all p < 0.01). Then, the players were divided into four subgroups (front row and locks, back row, inside backs and outside backs). RSA was significantly associated with the number of accelerations ( = -0.96, p < 001) and combat actions in front row and locks ( = -0.71, p=0.007). In the back row, RSA was correlated with distance ( = -0.96, p = 0.003) and the frequency of combat actions ( = -0.79, p = 0.04). In inside backs, RSA was significantly (all p < 0.01) correlated with distance ( = -0.81), number of accelerations ( = -0.94) and high-velocity running ( = -0.94), while in outside backs, RSA was associated with sprint frequency ( = -0.85) and the maximal in-game velocity reached ( = -0.89). These results demonstrate that RSA is associated with match running and combat activity performance (i) regardless of the position on the pitch and (ii) specifically for each player’s position by improving the corresponding activity profile.